1996
DOI: 10.1152/ajplung.1996.271.6.l924
|View full text |Cite
|
Sign up to set email alerts
|

Effects of U-37883A, a vascular selective KATP+ channel antagonist, in the pulmonary and hindlimb circulation

Abstract: The effects of the vascular selective nonsulfonylurea guanidine ATP-sensitive K+ (KATP+) channel-blocking agent U-37883A on vasodilator and vasoconstrictor responses were investigated in the pulmonary and hindlimb vascular beds of the cat. Under elevated tone conditions, both U-37883A and the sulfonylurea KATP+ antagonist, glibenclamide, attenuated pulmonary vasodilator responses to the KATP+ channel openers without altering responses to vasodilator agents that are reported to act by KATP(+)-independent mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Our findings are also consistent with experimental data in animals using a variety of techniques [18][19][20][21][22][23], which also suggest that vascular K ATP channels may not be critical to the regulation of basal vascular tone in skeletal muscle vasculature. Since the measurement of blood flow by forearm strain gauge plethysmography primarily reflects skeletal muscle perfusion, our findings have relevance to the skeletal muscle vascular bed.…”
Section: K Atp Channels and Resting Skeletal Muscle Blood Flowsupporting
confidence: 89%
“…Our findings are also consistent with experimental data in animals using a variety of techniques [18][19][20][21][22][23], which also suggest that vascular K ATP channels may not be critical to the regulation of basal vascular tone in skeletal muscle vasculature. Since the measurement of blood flow by forearm strain gauge plethysmography primarily reflects skeletal muscle perfusion, our findings have relevance to the skeletal muscle vascular bed.…”
Section: K Atp Channels and Resting Skeletal Muscle Blood Flowsupporting
confidence: 89%
“…Meisheri et al (78) and many others (16,27,28,54,69,97,99,108) have confirmed that, consistent with its in vitro profile, PNU-37883A antagonizes the hypotensive and vasodilatory effects of chemically different K-ATP channel openers in intact animals. In anesthetized cats, PNU-37883A (3.3 mg/kg i.v.)…”
Section: In Vivo K-atp Channel Opener Reversal and Interactionsmentioning
confidence: 68%
“…; 54), whereas a more natriuretic dose of 10 mg/kg transiently increased blood pressure and reduced heart rate (52). Compared with these species, in anesthetized cats K-ATP blocking doses of PNU-37883A (Յ5 mg/kg) minimally affected basal blood pressure, heart rate, or vascular resistance (16)(17)(18)(19)27,28,78,99).…”
Section: In Vivo Cardiovascular Actionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glibenclamide can also increase resistance in the mesenteric and renal vasculature, and in some skeletal muscle preparations [146][147][148]. However K ATP channels appear to make little contribution to resting tone in the pulmonary or cerebral circulations [141,[149][150][151].…”
Section: Functional Rolesmentioning
confidence: 99%